A facile hydrothermal approach for the density tunable growth of ZnO nanowires and their electrical characterizations. Issue 1 (December 2017) - Boubenia, S.; Dahiya, A.; Poulin-Vittrant, G.; Morini, F.; Nadaud, K.; Alquier, D.
Abstract Controlling properties of one-dimensional (1D) semiconducting nanostructures is essential for the advancement of electronic devices. In this work, we present a low-temperature hydrothermal growth process enabling density control of aligned high aspect ratio ZnO nanowires (NWs) on seedless Au surface. A two order of magnitude change in ZnO NW density is demonstratedvia careful control of the ammonium hydroxide concentration (NH4 OH) in the solution. Based on the experimental observations, we further, hypothesized the growth mechanism leading to the density controlled growth of ZnO NWs. Moreover, the effect of NH4 OH on the electrical properties of ZnO NWs, such as doping and field-effect mobility, is thoroughly investigated by fabricating single nanowire field-effect transistors. The electrical study shows the increase of free charge density while decrease of mobility in ZnO NWs with the increase of NH4 OH concentration in the growth solution. These findings show that NH4 OH can be used for simultaneous tuning of the NW density and electrical properties of the ZnO NWs grown by hydrothermal approach. The present work will guide the engineers and researchers to produce low-temperature density controlled aligned 1D ZnO NWs over wide range of substrates, including plastics, with tunable electrical properties.